Chemical constituents from Silene schimperiana Boiss. belonging to caryophyllaceae and their chemotaxonomic significance. (October 2020) - Hussein, Ismail A.; Srivedavyasasri, Radhakrishnan; El-Hela, Atef A.; Mohammad, Abd-Elsalam I.; Ross, Samir A.
Abstract: Phytochemical investigation of Silene schimperiana Boiss. ethanolic extract led to the isolation of fifteen compounds (1–15 ). The isolated compounds were identified by their NMR, MS spectral data analyses and comparing with published data as: vanillic acid (1 ), ferulic acid (2 ), caffeic acid (3 ), ethyl ferulate (4 ), apigenin (5 ), hesperetin (6 ), diosmetin (7 ), luteolin (8 ), kaempferol (9 ), quercetin (10 ), ecdysterone (11 ), hesperedin (12 ), diosmin (13 ), kaempferol-3- O -rutinoside (14 ) and rutin (15 ). The lack of chemical and biological investigations on this plant encouraged us to carry out the above-mentioned work. Highlights: This manuscript deals with isolation and identification of secondary metabolites from Silene schimperiana. This is the first report on isolation of chemical entities. Manuscript also establishes plant chemotaxonomy of the genus Silene.